Modeling of Spatial Inhomogeneity of Free Charge Carriers in Measuring Procedure of Their Local Concentration - O. K. Gusev (Наука и техника, 2004)
The paper presents results of the proposed generalized procedure in respect of measuring parameters of free charge carriers in the prescribed area of non-homogeneous object. It is shown that while solving measuring tasks on determination of their concentration non-homogeneous objects having boundaries between areas with various prevailing types of charge carriers can be modeled by division in body of interacting homogeneous areas. Realization of this model is executed by means of measuring procedure selection, identification of charge carrier type in the corresponding homogeneous area and taking measurements in accordance with the method which is based on the homogeneous object model.